Correlation of D-Dimer level with outcome in traumatic brain injury - Subedi, Pradip Prasad; Shilpakar, Sushil Krishna (Journal of Society of Surgeons of Nepal, 2016)
Introduction: Traumatic brain injury (TBI) is a common neurosurgical emergency and a common public health problem with high mortality and long term morbidity. The cost incurred by TBI is immense. The major determinant of outcome following TBI is the severity of the primary injury. However, secondary injuries including coagulopathy are treatable prognostic factors. Many studies have revealed that coagulopathy of trauma depicted by increasing level of D-dimer is associated with poor prognosis in TBI. So, early dectection and correction of such abnormality is very important in management of TBI. Methods: This is a prospective observational study conducted at Department of Surgery TUTH (Tribhuvan University Teaching Hospital), Kathmandu,Nepal over a period of one year. One hundred and forty eight patients of TBI were included in the study. Clinical profile of the patients and D-dimer level were monitored during the hospital course. D-dimer level was correlated with outcome variables including duration of hospital stay, duration of Intensive care unit (ICU) stay and Glasgow outcome scale (GOS). Results: A total of 194 patients were admitted with the diagnosis of traumatic brain injury during the study period and out of them 148 patients were enrolled for the study. Out of 148 patients one hundred and twenty (81.1%) were males and twenty eight (18.9%) were females. The mean age was 29.71±18.07 and the age ranged from 1 to 78 years. Seventy (47.3%) patient were between 21 to 40 years of age. The mean duration of hospital stay was 9.83±13.58 days and the mean duration of ICU stay was 3.78±7.06 days. Contusion was the most common lesion in our patients. Of the patients studied 111 patients (75%) had good recovery with GOS of 5, 9 patients (6.1%) had GOS of 4, 6 patients (4.1%) had GOS of 3, 1 patients (0.7%) had GOS of 2 and 21 patients (14.1%) had GOS of 1. Normal D-dimer was seen in 102 patients (68.9%) and elevated D-dimer in 46 patients (31.1%). Man –Whitney test shows higher D-dimer levels positively correlated with duration of hospital stay, duration of ICU stay and Glasgow Outcome Scale. Pearson chi-square test revealed higher levels of D-dimer correlated with grade of injury but not with mode of injury. Conclusion: D-dimer is elevated in significant proportion of patients with TBI and abnormal D-dimer level is associated with poor outcome in TBI. Journal of Society of Surgeons of Nepal Vol.17(1) 2014: 21-30